Analysis of 2G and 4G Network Quality on Cross Roads in Lembah Gumanti District - Yuhanef , Afrizal; Candra, Dikky; Musthaf, Muhammad Isham; setiawan, Herry (Brilliance: Research of Artificial Intelligence, 2024)
Lembah Gumanti Sub-District is one of the sub-districts in Solok Regency where people are on average separated from each other so that they spread out from one another. This is different from people who live in urban areas where they are close to one another. In addition, this area is dominant with hills and trees causing a performance degredation in 2G and 4G network performance. This study aims to find out how the quality of the 2G and 4G network of Telkomsel operators on the causeway in Lembah Gumanti District where data collection is carried out by means of a drive test using Tems pocket. The results showed that for the 2G network on RxLev it still showed poor results while on RxQual it showed good results. While making a call there were also 2 drop calls from 9 call attempts. Meanwhile for the 4G network the RSRP and SINR parameters showed poor results. Therefore, an increase in network performance is needed to increase people's satisfaction in the area.